THE FATWAS OF MAJELIS ULAMA INDONESIA ON THE AHMADIYAH DOCTRINES - Lilik Rofiqoh (Asia-Pacific Journal on Religion and Society, 2021)
This paper discusses two relevant fatwas and corresponding recommendations by Indonesian’s Ulema Council (Majlis Ulama Indonesia: MUI) on the doctrines of Ahmadiyah. In doing so, it takes the historical background of the issue of the fatwas along with its political context. MUI in issuing the fatwa received the full political support of the New Order government, which at that time was highly concerned with the national security and stability. Moreover, Indonesia did not seem able to reject the influence of the transnational Islamic countries’ policy, which stronglydemanded that Ahmadiyah must be banned from any Muslim country. A strong influence of particularly the government has created distrust in the MUI’s authority as an Islamic scholar organization that was politically notsterilized. Many have doubted that MUI’s fatwa was genuine and/or even effectively binding, particularly when its fatwa dealt with the status of sects within Islam–whether or not they are heretic.